알루미늄 5083의 피로균열 진전에 따른 수명예측 및 비파괴평가 - 남기우(KI-WOO NAM) (Han-guk haeyang gonghak hoeji (Online), 2001)
fatigue life and nondestructive evaluation were examined experimentally using surface crack specimen and compact tension specimen of 5083 aluminium alloy. Acoustic emission signals emanated during failure of aluminum alloys has been the subject of numerous investigations. Possible sources of AE during deformation have been suggested as the dislocations, fracture of brittle particles and debonding of these particles from the alloy matrix. Fatigue life and penetration behavior of long surface crack can be evaluated quantitatively using K values proposed by authors. The influence of stress ratio on the frequency characteristics of AE signals were investigated.